1968
DOI: 10.1111/j.1537-2995.1968.tb02396.x
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Study of the Safety of Pooled Plasma Stored in the Liquid State at 30–32 C for Six Months

Abstract: A prospective, controlled study of the frequency of hepatitis following transfusion of commercial pooled plasma, stored for at least six months in the liquid state at 30–32 C was performed, using 5 per cent albumin as a control solution. Twelve of 120 plasma recipients developed hepatitis. None of the 46 control subjects developed hepatitis. Fifty per cent of the hepatitis cases were icteric (total serum bilirubin greater than 2.0 mg/100 ml). All of the instances of hepatitis were confirmed by liver biopsy. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1969
1969
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…This became evident in a very thoroughly executed, comprehensive double blind study (with albumin as control) by REDEKER [1164,1638]. He found a total hepatitis frequency of 10%.…”
Section: Fresh Plasmamentioning
confidence: 89%
“…This became evident in a very thoroughly executed, comprehensive double blind study (with albumin as control) by REDEKER [1164,1638]. He found a total hepatitis frequency of 10%.…”
Section: Fresh Plasmamentioning
confidence: 89%
“…Attempts to inactivate the causative agent of the hepatitis by a variety of chemical and physical treatments failed to find a fully satisfactory method, but ultraviolet radiation or storage at room temperature for at least 6 months was believed to diminish the risk . There was considerable debate about this approach until Redeker and colleagues performed a controlled prospective study of plasma that had been irradiated and stored at room temperature and demonstrated a 10% incidence of hepatitis in recipients of the plasma but no hepatitis in recipients of human albumin that had been heated at 60°C for 10 hours. Based on this study, the Committee on Plasma and Plasma Substitutes of the Division of Medical Sciences, National Research Council, recommended that “the use of whole, pooled human plasma be discouraged and even discontinued unless a clear‐cut case can be made for its unique requirements.” We examine herein the markers of hepatitis in commercial pooled NHP from the 1960s.…”
mentioning
confidence: 99%
“…These findings might not apply in countries with less strict control of commercially available whole blood and blood extracts, but hepatitis ratios of 10-15% per unit of transfused blood now belong to the past since HBsAG checks are internationally instituted [16].…”
Section: Commentsmentioning
confidence: 98%